2016
DOI: 10.1002/2016gl067752
|View full text |Cite
|
Sign up to set email alerts
|

Plasma clouds and snowplows: Bulk plasma escape from Mars observed by MAVEN

Abstract: We present initial Mars Atmosphere and Volatile EvolutioN (MAVEN) observations and preliminary interpretation of bulk plasma loss from Mars. MAVEN particle and field measurements show that planetary heavy ions derived from the Martian atmosphere can escape in the form of discrete coherent structures or “clouds.” The ions in these clouds are unmagnetized or weakly magnetized, have velocities well above the escape speed, and lie directly downstream from magnetic field amplifications, suggesting a “snowplow” effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 35 publications
3
47
0
Order By: Relevance
“…Therefore, magnetic fields penetrating into the Martian magnetosphere can drag the bulk ionospheric ions with E × B drift motion. On the other hand, Halekas et al () observed the plasma clouds caused by “snowplow” effect which is also effective in the −E hemisphere. In this case, ions appear to be unmagnetized and they are accelerated by the polarization electric fields, leading to the same energy acceleration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, magnetic fields penetrating into the Martian magnetosphere can drag the bulk ionospheric ions with E × B drift motion. On the other hand, Halekas et al () observed the plasma clouds caused by “snowplow” effect which is also effective in the −E hemisphere. In this case, ions appear to be unmagnetized and they are accelerated by the polarization electric fields, leading to the same energy acceleration.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the interspersed populations with solar wind and magnetospheric origins must indicate either complex spatial structure or large amplitude fluctuations in the position of the boundary. These could represent shear‐driven instabilities such as Kelvin‐Helmholtz [ Penz et al ., ] and/or bulk loss of clouds of magnetosphere plasma [ Halekas et al ., ]. Inside the magnetosphere, energy‐time dispersed ions [ Halekas et al ., ] appear throughout the magnetosphere, suggesting acceleration by significant electric fields, possibly associated with the upstream and/or sheath dynamics.…”
Section: Maven Solar Wind Ion Analyzer (Swia) Measurements and In‐flimentioning
confidence: 99%
“…At Mars, observations of magnetic reconnection (Dubinin et al, 2008;Eastwood et al, 2008;Harada et al, 2015aHarada et al, , 2017, flux rope formation (DiBraccio et al, 2015;Eastwood et al, 2012;Hara et al, 2017), current sheet flapping , Marsward and tailward ion flows (Harada et al, 2015b), magnetic lobe dependence on IMF orientation Romanelli et al, 2015) and ionosphere magnetization , and bulk plasma escape (e.g., Brain et al, 2010;Halekas et al, 2016) have been reported in the magnetotail. At Mars, observations of magnetic reconnection (Dubinin et al, 2008;Eastwood et al, 2008;Harada et al, 2015aHarada et al, , 2017, flux rope formation (DiBraccio et al, 2015;Eastwood et al, 2012;Hara et al, 2017), current sheet flapping , Marsward and tailward ion flows (Harada et al, 2015b), magnetic lobe dependence on IMF orientation Romanelli et al, 2015) and ionosphere magnetization , and bulk plasma escape (e.g., Brain et al, 2010;Halekas et al, 2016) have been reported in the magnetotail.…”
Section: 1029/2018gl077251mentioning
confidence: 99%